HOMINISASI DAN HUMANISASI: TINJAUAN KRITIS ATAS KONSEP PENDIDIKAN DRIYARKARA - Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2015)
Humanisation is the basic concept of education, in the opinion of Driyarkara. This concept is the foundation of a number of critical thoughts by Driyarkara in matters of education, which can be perceived in a frame of philosophical and theological reflections. Philosophy and theology are considere to be the main instruments when one discusses education. Though this theory is rationally upon as most superbe, which is not to be discussed what so ever. On the contrary, educations is a product of a discourse, which has to be studied in a critical way, in order to forestall a mismanagement of dogmatical truth.